2017
DOI: 10.1111/1755-5922.12252
|View full text |Cite
|
Sign up to set email alerts
|

The significance of the washout period in preconditioning

Abstract: PKA activation before regional ischaemia is a prerequisite for cardioprotection in both B2PC and IPC. However, ROS was crucial only in IPC. Kinase activation during the washout phase of IPC and B2PC, albeit different, affords the same cardioprotective response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The requirement for PKB activation in cardioprotection was first demonstrated by Tong et al who reported that its inhibition during a preconditioning stimulus abolished protection. These results were subsequently confirmed by Salie et al . The role of ERK activation during preconditioning was less certain, and conflicting data were reported …”
Section: Risk Pathwaymentioning
confidence: 56%
“…The requirement for PKB activation in cardioprotection was first demonstrated by Tong et al who reported that its inhibition during a preconditioning stimulus abolished protection. These results were subsequently confirmed by Salie et al . The role of ERK activation during preconditioning was less certain, and conflicting data were reported …”
Section: Risk Pathwaymentioning
confidence: 56%
“…Apparently, a short (5 min) washout period, or its absence, determines the impact of the elevated cAMP on the myocardial injury during I/R. Thus, Salie et al [ 47 ] have recently shown in experiments on isolated rat heart that during the 5 min washout period after IP induced by a 5 min global ischaemia, activation of the cell survival kinases, such as p38MAPK, JNKp54/p46, Akt and extracellular signal-regulated kinase (ERK), takes place that might determine the cardioprotective effect of PKA. Others have suggested that the cAMP-dependent antiarrhythmic effect of IP is mediated by enhancing vagal influences [ 41 ].…”
Section: Discussionmentioning
confidence: 99%